On the Number of Membranes in Unary P Systems - Rudolf Freund; Andreas Klein; Martin Kutrib (Electronic Proceedings in Theoretical Computer Science, 2009)
We consider P systems with a linear membrane structure working on objects over a unary alphabet using sets of rules resembling homomorphisms. Such a restricted variant of P systems allows for a unique minimal representation of the generated unary language and in that way for an effective solution of the equivalence problem. Moreover, we examine the descriptional complexity of unary P systems with respect to the number of membranes.